2006
DOI: 10.1529/biophysj.105.079186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solvent on the Structure of the Alzheimer Amyloid-β(25–35) Peptide

Abstract: The free energy landscape for folding of the Alzheimer's amyloid-beta(25-35) peptide is explored using replica exchange molecular dynamics in both pure water and in HFIP/water cosolvent. This amphiphilic peptide is a natural by-product of the Alzheimer's amyloid-beta(1-40) peptide and retains the toxicity of its full-length counterpart as well as the ability to aggregate into beta-sheet-rich fibrils. Our simulations reveal that the peptide preferentially populates a helical structure in apolar organic solvent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
184
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(209 citation statements)
references
References 60 publications
(264 reference statements)
18
184
0
Order By: Relevance
“…The first sequence (GSNKGAIIGLM) we studied corresponds to residues 25-35 of amyloid-β which is found in patients with Alzheimer's disease [23,[56][57][58]. The second sequence (KHMAGAAAAGA) corresponds to residues 110-120 of the amyloidogenic β-hairpin peptide of the Syrian hamster prion protein, H1 peptide [23].…”
Section: Secondary Structures In Amyloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first sequence (GSNKGAIIGLM) we studied corresponds to residues 25-35 of amyloid-β which is found in patients with Alzheimer's disease [23,[56][57][58]. The second sequence (KHMAGAAAAGA) corresponds to residues 110-120 of the amyloidogenic β-hairpin peptide of the Syrian hamster prion protein, H1 peptide [23].…”
Section: Secondary Structures In Amyloidsmentioning
confidence: 99%
“…[59,60] implicated in Parkinson's disease. Explicit solvent simulations and experiments have shown that these sequences assume a large amount of β and coiled conformations in aqueous environments whereas the α helix is their dominant conformational pattern in solvents that mimic the interior of membranes (e.g., hexafluoroisopropanol-water mixture) [23,24,56]. Figure 10 shows how R cutoff affects secondary structure content.…”
Section: Secondary Structures In Amyloidsmentioning
confidence: 99%
“…Another severe limitation of REMD is that the number of replicas increases rapidly with the size of the system, limiting its applicability to small all-atom systems in solvent such as the monomer of full-length Ab, and dimers and trimers of short fragments. [45][46][47][48] The use of implicit solvent and coarse-grained models lifts some of the limitations of both MD and REMD on two counts. First, by removing some of the dampening due to the collision with the solvent, they accelerate the sampling of the phase space by as much as two orders of magnitude.…”
Section: In Silico Approaches To Simulate Amyloid Aggregationmentioning
confidence: 99%
“…Aβ 25−35 is a peptide fragment that has been studied widely in both experiments [4][5][6][7][8][9] and simulations [10,11]. In the experiments, it has been shown that this fragment aggregates into β-structures [4][5][6].…”
Section: Simulation Systemsmentioning
confidence: 99%